FINANCIAL PLANNING OF BUSINESS ENTITIES IN THE FINANCIAL MANAGEMENT SYSTEM - Zhuk , O.I.; Tomashevska , A.V.; Boryshkevych , I. I. (The actual problems of regional economy development, 2022)
The purpose of this article is to clarify the essence of the category of “financial planning”, to determine the main tasks, principles, directions and process of financial planning, as well as to study the place of financial planning in the financial management system of the entity.The article examines and systematizes the views of scholars on the interpretation of the concept of “financial planning”. Based on the research, the proposed refined definition of this category is proposed: “financial planning” - the process of managing financial resources, which aims to implement financial policy, achieve financial strategy goals, improve financial management and strengthen the financial condition of the entity.The main tasks of financial planning are determined: ensuring the functioning of the enterprise with the necessary financial resources; identification of funding sources; determining areas for efficient use and investment of capital; preparation of financial plans, analysis and control over their implementation; ensuring financial stability, solvency and creditworthiness of the enterprise; control over the use of financial resources. Implementation of tasks will ensure optimal management of financial resources.The principles of financial planning are substantiated: scientific, comprehensive, systematic, efficient, reliable, understandable. Adherence to these principles will make it possible to achieve the goals of financial planning. The directions of financial planning are considered and characterized: strategic financial planning, current financial planning, operational financial planning. The process of financial planning is described, which includes assessment and analysis of the financial environment of the entity, financial policy development, financial strategy development, development of current and operational financial plans, evaluation of results, which will help systematize and improve the organizational work of financial planning.The importance of financial planning in the system of financial management is determined.